A comparative study of the American Society for Reproductive Medicine and European Society of Human Reproduction and Embryology classification systems in the diagnosis and management of Müllerian anomalies: insights from a case series - V., Madhu Priya; Peethamabaran, Priyanka; Datti, Sujata N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Mullerian anomalies, congenital malformations of the female genital tract, arise from defective development, fusion, or resorption of Mullerian ducts and contribute to infertility, recurrent pregnancy loss, and primary amenorrhea. With a prevalence of 6.7% in the general population, accurate classification and diagnosis are crucial for effective management. This study compares the American Society for Reproductive Medicine (ASRM) and European Society of Human Reproduction and Embryology (ESHRE) classification systems using a prospective analysis of 12 cases. The ASRM’s simplicity contrasts with the ESHRE’s anatomical precision, but the latter struggles with complex anomalies. Findings reveal 41% of cases classified as hypoplastic uterus under ESHRE, with 25% remaining unclassifiable under ASRM. The study underscores the limitations of current systems in addressing complex anomalies involving vaginal and cervical deviations. It calls for a universal classification system integrating embryology, anatomy, and clinical insights for better diagnosis and treatment.